Bearing Capacity Of Cold-Formed Unlipped Channels With Restrained Flanges - Eof And Iof Load Cases - Janarthanan, B.; Gunalan, S.; Mahendran, M. (Nordic Steel Construction Conference 2015, 2015)
The current cold-formed steel specifications (AISI S100, AS/NZS 4600 and Euro-code) do not include any design rules to determine the bearing capacities of unlipped channel sections subjected to one flange loadings when their flanges are fastened to supports. Hence an experimental study consisting of 28 tests was conducted to determine the bearing capacities of these sections used in floor systems. Using the results from this study, a new equation was proposed within the AISI S100 guidelines to determine the bearing capacities of cold-formed unlipped channels. A new design rule was also proposed based on the direct strength method.